The Open Innovation Paradigm and the Semantic Web: an Ontology for Distributed Product Innovation - Meersman, Davor; Dillon, Tharam S. (Springer, 2010)
In this paper we introduce an ontology specifically designed for product innovation. We discuss the specifics and advantages of domain ontology construction for product innovation. We then look at the application ofthe framework to the scuba diving equipment manufacturing industry domain.